COVID-19 in patients with pulmonary alveolar proteinosis: a European multicentre study. Issue 1 (3rd January 2023) - Papiris, Spyros A.; Campo, Ilaria; Mariani, Francesca; Kallieri, Maria; Kolilekas, Lykourgos; Papaioannou, Andriana I.; Gonca Chousein, Efsun; Cetinkaya, Erdogan; Bonella, Francesco; Borie, Raphael; Kokosi, Maria; Pickworth, Thomas; et al.
Granulocyte–macrophage colony-stimulating factor (GM-CSF) signalling is essential in both alveolar macrophage (AM) differentiation and activation of lung immune cells [1]. Differentiated AMs are crucial in both the elimination of alveolar microbes and surfactant clearance. The disruption of the GM-CSF axis in AMs leads to the development of pulmonary alveolar proteinosis (PAP) [1]. In the majority of patients, this relates to the presence of autoantibodies against GM-CSF (autoimmune (a)PAP) but there are multiple other causes [1–3]. GM-CSF-deficient animals may have impaired lung inflammatory response to commensal microbes and humans with PAP may occasionally develop opportunistic lung infections [4]. The mainstay of pharmacological treatment in aPAP is inhaled GM-CSF (iGM-CSF), which is off-label but increasingly used worldwide [5–9]. Adult PAP patients experience similar #COVID19 rates to the general population, and high rates of hospitalisation and deaths, underscoring their vulnerability and the need for measures to prevent infection. The impact of iGM-CSF must be considered. https://bit.ly/3M0wKnZ